2023
DOI: 10.1088/1742-6596/2521/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Properties of concrete with glass fibre reinforced polymer waste as partial replacement of fine aggregate

Abstract: The proper disposal of fibre waste products is a significant issue for the GFRP industries; as a result, the reuse and recycling of these waste products require sustainable solutions. Given that FRP materials, especially those created with thermosetting resins, cannot be reprocessed, so the majority of thermosetting FRP waste will be dumped in landfills. Innovative approaches are thus required to manage waste. This study investigates the performance of the FRP waste, known as Glass Fibre Reinforced Polymer (GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…As the increase in mechanical strength was observed after 90 days of curing, it can be inferred that this behaviour is a result of the pozzolanic reactivity of GFRPW. Baturki et al reported that GFRPW exhibits a high pozzolanic activity, which is mainly controlled by its silicate content and fineness (54).…”
Section: Compressive Strengthmentioning
confidence: 99%
“…As the increase in mechanical strength was observed after 90 days of curing, it can be inferred that this behaviour is a result of the pozzolanic reactivity of GFRPW. Baturki et al reported that GFRPW exhibits a high pozzolanic activity, which is mainly controlled by its silicate content and fineness (54).…”
Section: Compressive Strengthmentioning
confidence: 99%